Latin and Music in the Early Modern Era : Education, Theory, Composition, Performance and Reception - Forgács, Robert (Classical Studies E-Books Online, Collection 2021, ISBN: 9789004441040., 2021)
Situating the close relationship between Latin and music within its historical context, this volume presents an overview of Latin and music in the educational system of the time - schools, choir schools and universities - and the development and pervasive influence of musical humanism. This influence is seen primarily in the writings of music theorists, the documents of dedication found in music publications and above all in the settings of classical and Neo-Latin texts as well as in some liturgical and extra-liturgical ones. Discussion of this repertoire forms the centre of the volume. The emphasis is on practical matters: the study of Latin and music, and the music's composition, performance and reception.